Brokerage and closure - Burt, Ronald S. (Oxford University Press, 2005)
Social Capital, the advantage created by location in social structure, is a critical element in business strategy. Who has it, how it works, and how to develop it have become key questions as markets, organizations, and careers become more and more dependent on informal, discretionary relationships. The formal organization deals with accountability; Everything else flows through the informal: advice, coordination,